(untitled) (Journal of Scientific Research, 2022)
Alkoxy group substituted compounds of acetanilide are found to have pharmacological and industrial importance. Synthesis of alkoxy substituted acetanilides via conventional thermal methods involves multi-step processes, formation of side products, and the poor yield of desired products. But, the vast literature studies reveal that electroorganic synthesis of alkoxy substituted acetanilide derivatives would be effectively carried out through electrochemical oxidation methods. The direct substitution of the ethoxy (alkoxy) group onto the aromatic ring, an electrophilic substitution, has not been attempted so far. This concept is taken as a preparatory attempt to find an alternative method to the tedious chemical route and to invent a direct method of introducing the ethoxy groups into the aromatic ring in a single step. A polarization study on acetanilide with ethanol as an electrolyte is carried out on platinum and graphite anodes to find out the oxidation potentials. Electrochemical ethoxylation of acetanilide at the platinum electrode is done by the Potentiostatic method using the oxidation potentials. The products are separated using preparative TLC and purified with suitable solvents. The products are characterized by UV, IR, NMR, and Mass spectra.